Does Stockholm Syndrome Exist in Lebanon? Results of a Cross-Sectional Study Considering the Factors Associated With Violence Against Women in a Lebanese Representative Sample - Rahme, Clara (Journal of interpersonal violence, 2021)
The aim of this study is to validate the Stockholm syndrome scale (SSS) in Arabic, assess the correlation of the Stockholm syndrome in women who are victims of domestic violence, and evaluate the factors that enhance the level of violation among a representative sample of the Lebanese population. This is a cross-sectional study conducted on Lebanese women between September and December 2018. Participants enrolled in this study were from all of Lebanon’s governorates and selected using an equitable representative sample. Being divorced (β = 9.83); with low educational level (β = 5.47); having a partner that takes substance (β = 16.17); addicted to alcohol (β = 8.21); addicted to gambling (β = 11.91); have a history of threats, violence, assaults, and crimes (β = 17.83); higher stressful life experiences (β = 0.75); and higher SSS score (β = 0.04) were significantly associated with higher partner physical and nonphysical abuse scale. For the validation of the SSS, five items (items 3, 20, 30, 38, and 40) were removed because none over-correlated with each other (r >.9), had a low load on the factors (<.3), or a weak commonality (<.3). SSS items converged on a seven-factor solution with Eigenvalues greater than 1, accounting for a total of 66.59% of the variance (α = .970). Our study revealed a positive association between the Stockholm syndrome and the violence against women and evaluated many factors that increase this association. Divorced women, with low educational level, having a partner addicted to alcohol, to illegal substance or to gambling, having a history of threats, violence, assaults, and crimes were more prone to experience physical and nonphysical abuse.